Internet and Social Media Usage Situations in Young People - Tel, Mikail; Bozkurt, Eyup; Tan, Cetin (Mashhad Univ Med Sciences, 2022)
Background: This research was conducted to determine the Internet and social media usage status of young people who do sports. Method: The research group consisted of 1521 (927 Males, 594 Females) young volunteers attending sports branches. As a data collection tool, an online questionnaire form was applied in which the participants' demographic information, social media usage status, Internet usage status and purposes were questioned. Results: It was determined that the research group used mobile phones frequently and at high rates for Internet access and social media. The participants' self-reported purposes of participating in the Internet included doing research, watching videos and movies, communicating with friends, making use of their spare time and following sports news, respectively. It was observed that the majority of the participants used the Internet almost every day. It was determined that the participants use Instagram, e-mail, Facebook and twitter, respectively, in social media, and 99.1% of them use social media for 1-3 hours every day. It was also revealed that the rate of using social media among women is higher than that among men, along with the increase in age, the rate of using Instagram and the rate of using email decreases, and the rate of using e-mail and Instagram increases in line with the increase in the level of education. Conclusion: It was observed that a large part of the research group frequently used the Internet and social media. It is recommended that the athletes use the Internet and social media to follow their professional development, sports news and organizations.
Keywords: Internet; Social Media; Young athletes